2023
DOI: 10.1128/spectrum.04102-22
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Insight into Microbiome and Antibiotic Resistance Genes of High Clinical Concern in Urban and Rural Hospital Wastewater of Northern India Origin: a Major Reservoir of Antimicrobial Resistance

Abstract: There is a paucity of research on detailed antibiotic resistome and microbiome diversity of Indian hospital wastewater. This study reports the predominance of clinically concerning ARGs such as the beta-lactamases bla NDM and bla OXA and the colistin resistance gene mcr and their association with the microbiome in six different Indian hospital wastewaters of both urban and rural origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 87 publications
1
7
0
1
Order By: Relevance
“…Na Índia, observou-se a predominância de genes de resistência contra aminoglicosídeos, macrolídeos, carbapenêmicos, trimetoprim e sulfonamidas em todas as amostras de esgoto testadas. Além disso, identificaram o gene mcr-5.1 de resistência à colistina móvel pela primeira vez no esgoto de um hospital indiano, demonstrando que houve uma mudança no perfil de resistência em efluentes hospitalares após a pandemia (Talat et al, 2023). Na China, utilizando metagenômica e bioinformática para analisar a comunidade microbiana de um esgoto hospitalar, Sun e colaboradores, em 2023, identificaram cerca de 1568 genes de resistência, correspondendo a 29 tipos e subtipos de antibióticos.…”
Section: Comercialização De Antimicrobianos E a Amrunclassified
“…Na Índia, observou-se a predominância de genes de resistência contra aminoglicosídeos, macrolídeos, carbapenêmicos, trimetoprim e sulfonamidas em todas as amostras de esgoto testadas. Além disso, identificaram o gene mcr-5.1 de resistência à colistina móvel pela primeira vez no esgoto de um hospital indiano, demonstrando que houve uma mudança no perfil de resistência em efluentes hospitalares após a pandemia (Talat et al, 2023). Na China, utilizando metagenômica e bioinformática para analisar a comunidade microbiana de um esgoto hospitalar, Sun e colaboradores, em 2023, identificaram cerca de 1568 genes de resistência, correspondendo a 29 tipos e subtipos de antibióticos.…”
Section: Comercialização De Antimicrobianos E a Amrunclassified
“…Cockroaches are often exposed to unsanitary environments, which can cause the spread of pathogenic microorganisms. Environmental pollution caused by wastewater discharge from hospitals and factories can become a hotspot for the emergence of “superbug” bacteria, through the acquisition of various antibiotic resistance genes as a result of horizontal gene transfer (Dai et al 2023; Talat et al 2023). Moreover, antibiotic resistance is a global public health emergency.…”
Section: Introductionmentioning
confidence: 99%
“…The study showed the presence of ARGs in all effluents and river water samples, demonstrating a complex method of acquiring ARGs in different bacterial communities. Recently, Talat and co-workers ( 31 ) provided a comprehensive overview of ARGs in hospital wastewater using metagenomics. The study uncovered many important clinical resistance gene classes, including beta-lactam, aminoglycosides, macrolide carbapenem, and sulfonamides, which were hosted by human pathogens, such as Pseudomonas aeruginosa , Acinetobacter baumannii , and Klebsiella pneumoniae , evinced the peril associated with ARG transmission in the environments ( 31 ).…”
Section: Introductionmentioning
confidence: 99%